Pengembangan Media Animasi Pada Pembelajaran Elektronika Siswa SMK - Yusnidah, Yusnidah (JKTP: Jurnal Kajian Teknologi Pendidikan, 2022)
The purpose of this development research is to describe the process of developing electronic learning animation media for SMK students, describe the validation of animation media development from material experts and electronic learning media experts of SMK students, describe the feasibility of electronic learning animation media for SMK students. The data used is descriptive qualitative which is the main data through instruments from material expert respondents and media experts. The research used the Borg and Gall models which were adjusted based on 6 stages due to the situation and conditions of the Covid-19 pandemic, namely needs analysis, product specification planning, product design, product validation, product revision, and dissemination. The use of Canva Pro was used in the animation media development process with the response of material experts obtained an overall average of 79.17%, the category of "very satisfactory". Meanwhile, from media / design experts obtained an overall average of 94.18%, the category is "very satisfactory". Thus, animation learning media as a research product is declared suitable for use in electronic learning for SMK students.AbstrakTujuan penelitian pengembangan ini adalah untuk mendeskripsikan proses pengembangan media animasi pembelajaran elektronika siswa SMK, mendeskripsikan validasi pengembangan media animasi dari ahli materi dan ahli media pembelajaran elektronika siswa SMK, mendeskripsikan kelayakan media animasi pembelajaran elektronika siswa SMK. Data yang digunakan merupakan deskriptif kualitatif yang merupakan data pokok melalui instrumen dari responden ahli materi dan ahli media. Penelitian menggunakan model Borg dan Gall yang disesuaikan berdasarkan 6 tahap karena situasi serta kondisi pandemi Covid-19 yakni analisis kebutuhan, perencanaan spesifikasi produk, perancangan produk, validasi produk, revisi produk, dan diseminasi. Penggunaan Canva Pro digunakan pada proses pengembangan media animasi dengan respon ahli materi diperoleh rata- rata keseluruhan 79,17%, kategori “sangat memuaskan”. Sedangkan dari ahli media/ desain diperoleh rata- rata keseluruhan 94,18%, kategori “sangat memuaskan”. Dengan demikian media pembelajaran animasi sebagai produk penelitian dinyatakan layak digunakan pada pembelajaran elektronika siswa SMK.